An Error Analysis of Grammatical Errors in EFL Students' Speaking Performance - Permatasari, A.A. Sg. Candra; Ningrum, Ida Ayu Fortuna (Journal of English Language and Education, 2026)
This study aims to analyze grammatical errors produced by Indonesian EFL university students in their English-speaking assignments. The data were obtained from students’ speaking videos collected from mid-term and final tests at Universitas Pendidikan Nasional, Denpasar, Bali. Using a qualitative descriptive approach, the study employed error analysis based on the surface strategy taxonomy proposed by Dulay, Burt, and Krashen, which classifies errors into omission, addition, misformation, and misordering. A total of 50 grammatical errors were identified, with misformation errors occurring most frequently, followed by omission, addition, and misordering errors. The findings indicate that students experience difficulties in selecting appropriate grammatical forms during spontaneous oral production, particularly in verb forms, subject–verb agreement, comparative constructions, and sentence structure. These errors reflect learners’ developing interlanguage and their tendency to prioritize fluency over grammatical accuracy in spoken communication. The study suggests that explicit grammar instruction integrated into speaking activities and systematic corrective feedback may help improve students’ grammatical accuracy in English speaking performance.